2021
DOI: 10.1128/mbio.03225-20
|View full text |Cite
|
Sign up to set email alerts
|

Puf4 Mediates Post-transcriptional Regulation of Cell Wall Biosynthesis and Caspofungin Resistance in Cryptococcus neoformans

Abstract: The human fungal pathogen Cryptococcus neoformans is intrinsically resistant to the echinocandin antifungal drug caspofungin, which targets the β-1,3-glucan synthase encoded by FKS1. Echinocandins have been on the market for 20 years, yet they are the newest class of antifungal drugs. Analysis of a C. neoformans puf4Δ mutant, lacking the pumilio/FBF RNA binding protein family member Puf4, revealed exacerbated caspofungin resistance. In contrast, overexpression of PUF4 resulted in caspofungin sensitivity. The F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…6 c,d; Additional File 1 : Fig. S6f), Puf4 (UGUANANUA [ 31 , 48 , 49 ]) (Fig. 6 e,f; Additional File 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 c,d; Additional File 1 : Fig. S6f), Puf4 (UGUANANUA [ 31 , 48 , 49 ]) (Fig. 6 e,f; Additional File 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the RBPs that interact with Rmt5 is the pumilio/FBF RBP family member Puf4. Our previous work showed that Puf4 is critical in post-transcriptionally regulating caspofungin resistance (28). Combined with our current Rmt5 interactome data set, we speculate that Rmt5 fine-tunes virulence- and antifungal resistance-associated cellular functions via methylating Puf4 and other effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown overnight at 37°C in YPD broth and then washed with sterile distilled water. The cells were stained with calcofluor white, wheat germ agglutinin (fluorescein isothiocyanate conjugated), eosin Y, and concanavalin A (Alexa Fluor 488 conjugated) as described previously (28) to detect cell wall chitin, exposed chitooligomers, chitosan, and mannoproteins, respectively. Flow cytometry data were acquired using a BD LSRFortessa cell analyzer and analyzed using FlowJo v10.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…Transcript and protein levels do not always correlate, and unstable mRNA can be translated more efficiently (60). In Cn lacking post-transcriptional gene regulator PUF4 , the FKS1 mRNA and Fks1p levels did not correspond (46). Unfortunately, we were unable to quantify α-glucan with the available methods, but the α-glucan synthase AGS was upregulated in old Cn , indicating that this glucan is likely also increased.…”
Section: Discussionmentioning
confidence: 99%